RELATIONSHIP PREGNANT WOMEN WITH PRE ECLAMPSIA AND BABY LOW BIRTH WEIGHT - Waruwu, Irwida; Novita, Regina Vidya Trias (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Preeclampsia is a pregnancy complication characterized by hypertension and proteinuria, which usually occurs after 20 weeks of pregnancy. This condition can have a major impact on the health of the mother and fetus, one of which is increasing the risk of low birth weight (LBW). This study aims to determine the relationship between preeclampsia and the incidence of LBW among pregnant women who experience preeclampsia. This study was conducted at RSU Bethesda Gunungsitoli starting from July 2024 to January 2025. This research method is quantitative descriptive analytic with a retrospective approach. Univariate and bivariate statistical analysis with the chi-square statistical test. The results of the bivariate test showed a significant relationship between preeclampsia and the incidence of LBW (p-value 0.001). Suggestions for respondents Pregnant women are expected to better understand the symptoms of preeclampsia, such as hypertension and swelling of the extremities, as well as the importance of early detection and routine control during pregnancy (ANC). Regular blood pressure checks are very important to detect the condition of preeclampsia early on.